Report of the Committee on Twenty Five Year's Perspective Plan for the Development of Rainfed Areas - Planning Commission (Planning Commission, 1997)
The Parliamentary Committee for the Department of Agriculture and Cooperation had desired that a 25 Year Perspective Plan may be developed for the development of rainfed areas of the country. In consultation with the Department of Agriculture and Cooperation, it was decided to constitute a Committee under Member(Agri.), Planning Commission to undertake this task and provide a plan for the consideration of the Government. the Committee was constituted on 20th July, 1994 under the Chairmanship of Dr. Jayant Patil, the then Member(Agri.), Planning Commission.
Planning Commission
Planning Commission Government of India